2020
DOI: 10.1101/2020.05.18.101972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioinformatic analysis for the identification of potential gene interactions and therapeutic targets in atrial fibrillation

Abstract: a These two authors contributed equally to this work Abstract Background: Atrial fibrillation (AF) is the most prevalent tachycardia. The major injuries caused by AF are systemic embolism and heart failure. Although AF therapies have evolved substantially in recent years, the success rate of sinus rhythm maintenance is relatively low. The reason is the incomplete understanding of the AF mechanisms. Material and method:In this study, profiles were downloaded from the GEO database (GSE79762).Bioinformatic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The current consensus is that electrical remodeling, inflammation, fibrosis as well as genetics are the major substrate for AF (34,35). In our analysis, these m6A-SNPs are involved in biological regulation and signaling, which may regulate the electrical remodeling, inflammation, fibrosis (36).…”
Section: Figurementioning
confidence: 79%
“…The current consensus is that electrical remodeling, inflammation, fibrosis as well as genetics are the major substrate for AF (34,35). In our analysis, these m6A-SNPs are involved in biological regulation and signaling, which may regulate the electrical remodeling, inflammation, fibrosis (36).…”
Section: Figurementioning
confidence: 79%
“…To explore the function of differential genes, the online bioinformatics tools Database for Annotation, Visualization, and Integrated Discovery (DAVID) were used to annotate the functions of GO and KEGG pathway enrichment analysis [20][21][22] .…”
Section: Gene Ontology (Go) and Kyoto Encyclopedia Of Genes Genomes (...mentioning
confidence: 99%
“…These pathways can also be used to target genes that might be involved in pathogenesis of atrial fibrillation and can be used as therapeutic targets and potential biomarkers. Biomarkers for atrial fibrillation are already being identified [ 129 , 130 ] and could be useful in clinical risk assessment and outcomes for individuals with atrial fibrillation.…”
Section: Conclusion Challenges and Future Directionsmentioning
confidence: 99%